A spatial exploring model for urban land ecological security based on a modified artificial bee colony algorithm - Wang, Haiying; Qin, Fen; Zhang, Xinchang (Ecological informatics, 2019)
Urban land ecological security plays an important role in alleviating human–land conflicts and in coordinating the development of natural and human resources and the environment. However, the subject of the present urban land ecological security is poorly studied. Given the circumstances, this paper presents a spatial exploring model for urban land ecological security (ULESM) based on the modified artificial bee colony algorithm (MABCA). The paper improves ABCA with a spatial grid, designed a grid-based ABCA calculation framework, ABCA's data structure, information-sharing mechanism and position selection strategy, introduces the model of spatial coupling and coordination degree for urban ecological security, and achieves spatial detection of ecologically hazardous areas. Taking Guangzhou as an example, this paper simulated the hazardous regions of the urban ecological land (assumed area: 50% of total area of Guangzhou), yielding favorable results. The results show that the ULESM based on MABCA exhibits an excellent global search and a rapid global-convergence speed, preventing a bee colony from being trapped in a local optimum. It can also effectively detect regions with urban land ecological hazards and provide intelligence-aided methods for decision making in urban ecological security and spatial planning [Display omitted] •A spatial exploring model for urban land ecological security based on the modified artificial bee colony algorithm is proposed.•The bee colony data structures, information-sharing mechanism, position selection mechanism, and dynamic role transition mechanism is designed or improved.•ULESM features good spatial aggregation ability to achieve high-accuracy result and extraordinary global search performance.•Urban land ecological security hidden areas can be simulated by using ULESM under the given spatial objective functions.